2020
DOI: 10.1589/jpts.32.375
|View full text |Cite
|
Sign up to set email alerts
|

Changes in social participation and life-space mobility in newly enrolled home-based rehabilitation users over 6 months

Abstract: This study aimed to examine whether we were able to measure changes in social participation and life-space mobility of newly enrolled home-based rehabilitation (HR) users by using the activities and participation components of the International Classification of Functioning, Disability and Health (ICF) and Life-Space Assessment (LSA) over a 6-months period. [Participants and Methods] We enrolled 47 HR users who had suffered from a stroke or other condition within the previous year. A 6-month prospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Previous studies have reported improved IADL in HR. 37 In our study, the FAI used to assess IADL was associated with severe life-space restrictions among HR users. Thus, providing HR support in this regard is necessary, as indicated in previous studies.…”
Section: Ability To Move and Adlmentioning
confidence: 63%
“…Previous studies have reported improved IADL in HR. 37 In our study, the FAI used to assess IADL was associated with severe life-space restrictions among HR users. Thus, providing HR support in this regard is necessary, as indicated in previous studies.…”
Section: Ability To Move and Adlmentioning
confidence: 63%
“…Despite having risk factors, the FIM score significantly improved from 108 to 115 points after intervention. Further, Kamioka et al reported significant improvements in the FIM score from 94.4 to 97.9 points after three-months of multicomponent home-based rehabilitation in older people 16) . The participants in our study showed an improved of FIM score by 7.0 points after three-months of intervention, despite having high scores at baseline.…”
Section: Discussionmentioning
confidence: 98%
“…The participants were aged 83.3 ± 5.9 years and mobility-related disability in frail older people. Kamioka et al reported a significant improvement of 5.0 points in LSA score after 6 months of multicomponent home-based rehabilitation in older people who had suffered a stroke or an injury in the past 1 year 16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An RCT study by Ito et al 16 ) reported that HR intervention based on the Management Tool for Daily Life Performance was effective in improving ADL and social participation. Moreover, a prospective cohort study by Kamioka et al 17 ) reported that HR users within 1 year of the onset of stroke or other conditions showed an improvement in ADL over 3 months, especially in walking, toileting, and bathing activities, as well as improvements in social participation and life-space mobility over 6 months. However, these studies targeted elderly participants requiring long-term care due to various diseases, while not specifically targeting stroke survivors.…”
Section: Introductionmentioning
confidence: 99%